Work Environment Conditions and Their Influence on Employee Performance within a Public Service Organization: Evidence from the Ambon City Environmental and Waste Management Agency - Muhammad Isa Pelu; Hendry Selanno; Jeanly Waisapy (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to examine the effects of physical and non-physical work environments on employee performance at the Ambon City Environmental and Waste Management Agency and to measure the magnitude of their partial and simultaneous influences on work outcomes. Methodology: This quantitative study employed structured questionnaires as research instruments, a survey method, and multiple linear regression analysis. Data were processed using IBM SPSS Statistics software. Respondents were all employees of the Ambon City Environmental and Waste Management Agency, selected through a census technique, and measured using Likert-scale items. Main Findings: The results show that the physical work environment significantly affects employee performance, while the non-physical work environment also has a positive and significant influence. Simultaneously, both variables strongly predict performance levels. Regression coefficients indicate that non-physical aspects contribute more dominantly, and the model explains a substantial proportion of performance variance among employees in the organization. These findings highlight the importance of improving workplace conditions in public sector institutions to enhance the quality of public service delivery and organizational responsiveness to community needs. Furthermore, a supportive work environment contributes not only to employee productivity but also to broader social welfare by enabling government agencies to perform their public duties more effectively. Novelty/Originality of this study: This study offers new empirical evidence from eastern Indonesia’s municipal environmental sector by integrating physical and non-physical workplace factors with integrity-related organizational issues. It advances existing knowledge by providing context-specific data for public agencies managing sanitation services and by supplying a practical model for targeted workplace improvement policies.